A Review on Phytochemical and Pharmacological activities of Syringodium isoetifolium - Kalaivani P; Kavitha D; Vanitha V (International Journal of Research in Pharmaceutical Sciences, 2020)
Seagrass are marine plants, grown in saline environments and fully submerged in the sea. They are widely distributed along the tropical and subtropical regions. A seagrass called, Syringodium isoetifolium comes under the family Cymodoceaceae, this grass is otherwise called as noodle grass. Phytochemical compounds such as flavonoids, terpenoids coumarins, xanthoproteins, sugars, carboxylic acids can be extracted by the solvents such as methanol, hexane, and acetone. Syringodium isoetifolium has pharmacological activities such as antioxidant, antihemolytic, antibacterial cytotoxicity, and antifungal activity. During photosynthesis, lacunal gas is discharged from lacunae, and it is composed of oxygen and nitrogen. Pheophytin a compound was isolated from the crude extract of Syringodium isoetifolium by treating it with human pathogens. Binding sites of the pathogen can be found by the Molecular docking study. In this article, we discuss about the phytochemical constituents, pharmacological activities, and morphological characteristics of Syringodium isoetifolium.